Percutaneous osteosynthesis of Galeazzi fracture-dislocation - Gadegone, Wasudeo M (Medknow Publications, 2010)
BACKGROUND: A Galeazzi fracture is defined as a fracture of the radius associated with dislocation of the distal radio-ulnar joint (DRUJ). The conventional surgical technique of nailing does not give enough stability and open reduction, internal fixation with the plate is associated with numerous complications. The stacked nailing for the management of these injuries provides adequate stability, maintains the relationship of the DRUJ and promotes uneventful union by closed technique. The purpose of this study is to evaluate the results of simple, user-friendly, low cost elastic stacked nailing for the management of Galeazzi fracture dislocation. MATERIALS AND METHODS: We treated 22 young adults with fresh Galeazzi fracture-dislocation of the forearm, from January 2004 to January 2008, by percutaneous fixation of fracture by stacked elastic nailing at our institute. There were 19 males and three females and the age group ranged from 20-56 years (average 35 years). Surgery was performed within 48 to 72 hours under the guidance of image intensifier. Medullary cavity was filled with two elastic titanium nails having unequal lengths and diameter. One nail acts as a reduction nail and the other acts as a stabilizing nail. The results were evaluated using Mikic criteria based on union, alignment, relationship of the DRUJ, and movements at the inferior radio ulnar joint, elbow and wrist. RESULTS: In six cases, following radiological union, nails in the radius were extracted between six to nine months after operation because of discomfort complained by the patient at site of insertion. After one year follow-up, 18 patients had excellent, four had fair results. CONCLUSION: Closed reduction and internal fixation of Galeazzi fracture by two elastic rods re-establishes the normal relationship of the fractured fragments and the DRUJ without repair of the ligaments. The stability is achieved by the flexibility and elasticity of the nails, crowding of the medullary canal and anchorage they gain in the radial diaphysis. Elastic nailing can produce excellent clinical results for Galeazzi fracture-dislocation. It has the advantages of technical simplicity, minimal cost, user-friendly instrumentation, and a short learning curve.